Law of Rape: Sec 63 of Bharatiya Nayay Sanhita: Does it require amendment? Yes. - Gupta , BD (Journal of Indian Academy of Forensic Medicine, 2024)
Asingle Judge bench of M. P. High Court has recently passed a judgment which is going to have long lasting repercussions in society and would particularly affect married women and would be married women. At the same time the Parliament has passed B.N.S. (Bharatiya Nayay Sanhita). The sec 63 and related sections about rape have given expansive definition of sexual intercourse. The referred judgment talks about this expansive definition of sexual intercourse and pronounces that now no sexual intercourse is unnatural. Aliberty is given to husband in the form of Exception-2 to indulge in so many sexual acts which were unnatural and unlawful till date. In my view this has happened without the knowledge and free and fair consent of concerned women folk. Paper discusses these issues and gives an amicable short solution to resolve the problem.